A political ideology of the Indonesian Islamic philanthropy institution: a case study of Suryakarta Beramal foundation - Agus Wahyu Triatmo; Ravik Karsidi; Drajat Tri Kartono; Suwarto Suwarto (Indonesian Journal of Islam and Muslim Societies, 2020)
This present research studies the ideologization practices of the Islamic philanthropy institution managed by the civil society in Indonesia: a case study of Suryakarta Beramal Foundation. A qualitative method with a case study approach was employed. Data was collected using in-depth interviews, observations and documentation techniques and then inductively analyzed. The results show that Suryakarta Beramal is a philanthropy institution ideologically affiliated withthe Tarbiyah movement. Most of the collected Islamic philanthropy funds: zakat, (alms-giving), infak (infaq), sadaqah (donation) and wakaf (religious endowment) were provided to finance the educational institution possessed by Suryakarta Beramal, except for poverty alleviation; the educational institution also functions as an ideologization medium. Ideologization was conducted through curriculum engineering, holding various events such as smart recharging, liqa, mabit, rihlah and halaqah and students’ habituation, starting from using uniforms for religious activities either at school or in the dormitory. The result of the ideologization is that the alumni of the school of Suryakarta Beramal became the loyalists of the Tarbiyah ideology and are affiliated with Partai Adil Makmur (PAM) (Just and Affluent Party) as the political wing of the Tarbiyah movement in Indonesia.